Biological controls for preventing food deterioration strategies for pre- and postharvest management - Sharma, Neeta (John Wiley & Sons Inc., 2014)
Various biotic factors cause diseases in crops, which result in food losses. Historically pesticide development has been instructive to us in terms of the benefits derived as well as the hazards that accompany their indiscriminate use. The application of fertilizers and pesticides to crops has become a norm in agricultural production, but this has led to resurgence in pests as they have developed resistance to such chemicals. Biological control of plant pests and pathogens is part of the solution to this problem. This is an area that continues to inspire research and development.